Reducing power ripple for multi-rotor wind energy systems using FOPDPI controllers - Habib Benbouhenni; Ilhami Colak; Z. M. S. Elbarbary; Shaik Mohammad Irshad (Scientific Reports)
Abstract Energy systems based on wind energy have now become a necessity due to their many advantages. However, using traditional turbines has several disadvantages, the most notable of which is the low performance and quality of the resulting energy. This work proposes an energy system based on the use of a multi-rotor wind turbine (MRWT) with a double-fed induction generator. In addition, to obtain high-quality power, a new control is used based on the development and modification of direct power control (DPC) based on proportional-integral (PI) controllers. This designed approach has many advantages, such as fast dynamic response, easy adjustment, high robustness, and ease of implementation. In this designed technique, the PI controller is dispensed with, and they are replaced by the designed fractional-order proportional-integral proportional derivative controller. This designed technique is based on power estimation, where the same estimation equations used in the DPC-PI technique are used. Robustness, high competence, and effectiveness in improving power quality are among the most prominent features of the designed technique compared to the DPC-PI approach and some research works. The designed technique was verified using MATLAB, comparing the results obtained in the case of different wind speed profiles with those using the DPC-PI approach. Numerical results demonstrated the efficacy of the designed technique over the DPC-PI approach, as the steady-state error and active power ripples were minimized in the first test by rates estimated at 44.72% and 46.67%, respectively. Also, the reactive power overshoot and ripples were reduced in the fifth test by rates calculated at 81.40% and 42.18%, respectively. On the other hand, the total harmonic distortion of the current was minimized by rates estimated in the five suggested tests at 33.80%, 34.88%, 11.52%, 37.58%, and 33.33%. These percentages show the strength of the performance and effectiveness of the designed technique in enhancing the robustness and efficiency of the MRWT system, making it a promising solution.